Social Responsibility and The Malaysian Legal Fraternity: Development Of Pro Bono Strategic Framework - Rangganathan, Geetharani (2009)
This dissertation focuses on Corporate Social Responsibility and the Malaysian legal fraternity, particularly, in relation to legal aid and pro bono legal services. There is ample literature written on Corporate Social Responsibility from numerous perspectives, primarily in relation to the corporate sector, but very limited articles have been written about the Social Responsibility of the Malaysian legal fraternity towards ensuring the availability of access to justice in terms of legal assistance to all members of the society. Thus, this paper seeks to provide insights into the Social Responsibility of the Malaysian legal fraternity, namely the Malaysian Bar Council, law firms and lawyers in terms of legal aid and pro bono legal services. The “People’s Judge”, Lord A.T. Denning once said, “In our society, if we are to maintain civilization as we know it, it is essential that each one of us does all he can to let justice be done”. This legal mantra depicts that the rule of law is not a luxury and that justice is not a side issue (Annan, 2004). The Malaysian Bar Council, however, has expressed its concern that a huge number of people in dire need of legal assistance, especially those charged with serious offences have been neglected. Ignorance of the law and the inability to engage a lawyer have contributed to impecunious people being deprived access to legal assistance, resulting in thousands of alleged accused pleading guilty ending up in them being caught in a legal quagmire with criminal records for the rest of their lives. The Bar Council Legal Aid Scheme is unable to assist many people as its reach is limited due to lack of resources, in terms of funds and volunteer lawyers. In light of the above scenario, this paper attempts to suggest a strategic framework for legal aid or pro bono work undertaken by the Bar Council through a comparative analysis of key themes and pro bono practices undertaken by the legal fraternities in England and Wales, Australia and Singapore. Further, this paper also seeks to explore potential collaborations or strategic relationships between the legal and business sectors in addressing the issue of lack of access to justice in terms of legal assistance through Corporate Social Responsibility initiatives of corporations.